Influence of permanent perpendicular magnetic field on the electrodeposition of nickel - Ebadi, M.; Alias, Y.; Basirun, Wan Jefrey (2009)
This work focuses on the electrodeposition of nickel from a Ni Watt's solution in presence and absence of a permanent perpendicular magnetic field (PPMF) to the cathode surface. It was found that the difference between the mass deposition were enhanced in the presence of PPMF (B = 4.4 T) and in absence of PPMF (B = 0) with increasing of current density (Am = 0.413 to 4.173 mg cm2 in 6 min). The thickness of deposited layers with PPMF was smaller than without PPMF. Therefore, the dense deposited layers were carried out from magneto-electrode position. The Ni Watt's solution contains thiourea as a brightener. The grain size of deposited nickel crystals decreased with PPMF compare to without PPMF. The deposited layers characterized by scanning electron microscopy, X-ray diffraction and atomic force microscopy.